Effect of Profitability Ratios on Stock Prices in Indonesian Transportation and Logistics Firms - Maria Novita Ayu Tuerah; Joanne Mangindaan; Sandra Ingried Asaloei (Research Trend in Technology and Management, 2026)
This study examines the effect of Return on Assets and Return on Equity on stock prices of transportation and logistics sector companies listed on the Indonesia Stock Exchange during 2020–2024. The research was motivated by the strategic role of the transportation and logistics sector in Indonesia’s economy and the inconsistent findings of previous studies regarding profitability ratios and stock prices. This study employed a quantitative associative approach using secondary data from audited annual financial reports and stock closing prices. Purposive sampling was used to select 12 companies, resulting in 55 observations after data transformation. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, partial significance tests, simultaneous significance tests, and coefficient of determination analysis. The results indicate that Return on Assets does not have a significant effect on stock prices, while Return on Equity has a significant positive effect. Simultaneously, both variables significantly affect stock prices. These findings suggest that investors place greater emphasis on equity profitability than asset efficiency in assessing stock value. This research contributes to the development of financial performance analysis, particularly in understanding stock price determinants in Indonesia’s transportation and logistics sector.